Mutagenic-sensitivity and variability induction in garden rose (Rosa × hybrida) - YADAV, HARENDRA; NAMITA; SINGH, M K; SINGH, KANWAR PAL; SINGH, BHUPINDER; PANWAR, SAPNA; MANDAL, B N; KUMAR, SUDHIR (The Indian Journal of Agricultural Sciences, 2025)
Mutation breeding is one of the most desirable breeding methods to enhance genetic variability and to improve economically important traits in ornamental crops. An induced mutation leading to altered phenotypes after a permanent heritable change in the structure of the genetic material is now established as a time saving and inexpensive approach for flower crop improvement. Gamma (γ)-irradiation induces changes in plant growth and flowering traits of flower crop plants. The present study was carried out during 2020–2022 at ICAR-Indian Agricultural Research Institute, New Delhi to induce the variability in rose (Rosa × hybrida L.) using gamma rays under in vivo conditions. Semi- hardwood cuttings of cv. Pusa Virangana were treated with gamma rays at different doses and it was observed that 100% cuttings were dried beyond 40 Gy doses of gamma rays. Gamma rays adversely affect plant growth (days to bud sprouting, plant height and internodal length. Maximum primary branches (6.0/plant) and plant spread (55.50 cm) were observed in 20 Gy treatment, however, leaf characters, viz. leaflet length and width and compound leaf area showed random effects. Leaflet apex margin found undulated type at 30 Gy comparisons to the other treatments and control. Flowering traits i.e. maximum flower stalk length (6.83 cm), number of flowers/plant (9.00), flower diameter (7.67 cm), number of petals/flower (30.00), petal size and single flower weight (5.09 g) were observed at 20 Gy of gamma rays. Two mutants were isolated from mutation population of cv. Pusa Virangana at 30 Gy (PVM-1) and 20 Gy (PVM-2) doses in in vivo mutagenesis. PVM-1 has bicolour, medium size, red purple group flower. PVM-2 has single colour, large size, red purple group flower, have greater number of petals and compact flower. Based on survival percentage after 30, 60 and 90 days of planting of cuttings, the lethal dose 50 (LD50) for gamma irradiation was determined using probit analysis values, which were 27.9, 16.2 and 11.2, respectively.